Aqueous Leaf Extract of Senduduk (Melastoma malabathricum L.) Could Improve the Physicochemical Properties of Beef Sausage Dough - Suharyanto Suharyanto; Henny Nuraini; Tuti Suryati; Irma Isnafia Arief; Dondin Sajuthi (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2020)
Improving comminuted meat products characteristics using a natural agent, such as phytochemicals, in order to replace the use of nitrite, have become a need due to the health reason. The quality of the sausage is also affected by the initial characteristics of the dough. Therefore, this research was conducted to investigate the effect of aqueous leaf extract of senduduk (Melastoma malabathricum L.) on the physicochemical properties of beef sausage dough. Different four formulas as treatment were employed to form the dough: formula A was as a control consisted of beef meat, vegetable oil, skim milk powder, tapioca, salt, phosphate, and seasoning; formula B was control added with extract 0.55%; formula C was control added with sodium nitrite 0.0011%, and formula D was control added with extract 0.55% and sodium nitrite 0.0011%. All ingredients were blended to be the dough. The result of the study denoted that the extract (B and D) significantly decreased (P<0.05) pH, and aw value with no difference in water content among the dough. The total phenolic content of the dough containing extract (B and D) was markedly higher (P<0.05) than were others. It increased significantly on antioxidant capacity, scavenging activity, and reduced the thiobarbituric acid reactive substances (TBARS) value of the dough. There was also no nitrite residual detected in all dough. In conclusion, the extract could improve the physicochemical properties of beef sausage dough and replace the use of nitrite in the dough.